Cross-gender Practices in Banyumasan Lengger Performances: The Dialectic of the Body and the Continuity of Tradition - Rahma Damayanti; Gunawan (Pusat Studi Gender Universitas Jember, 2026)
Cross-gender art has long been part of performing arts in Indonesia, one example being the lengger performance in the Tutupan Tradition in Tambaknegara Village, Banyumas Regency, which requires men to act as sinden and lengger dancers like women. However, amid changing times, this art form has begun to face challenges in the form of negative stigma associating it with deviant behavior such as LGBT. This paper aims to examine the existence of cross-gender as part of the social system of society by analyzing it using Anthony Giddens' structuration theory. Data collection was carried out from January to November using qualitative methods with a life history approach. Data was obtained through in-depth interviews, observation, and documentation. The results of the study show that cross-gender in the Sadran Covering Tradition is a structured part of the social system of society. Being cross-gender is not merely a personal choice, but rather the fulfillment of traditional demands that prohibit women from appearing on stage. The existence of cross-gender dancers is a manifestation of Giddens' duality of structure, where individuals are not only shaped by social structures, but also actively reproduce and maintain those structures